Analyses of the insulating characteristics of mineral oil at operating conditions - Taslak, Eyup; Arikan, Oktay; Kumru, Celal Fadil; Kalenderli, Ozcan (SPRINGER, 2018)
Experimental data on the electrical insulation in mineral oil are important for the optimal design of high voltage equipment in industrial power systems. In this paper, dielectric properties of mineral oil including breakdown voltage, dielectric dissipation factor, dielectric losses, relative permittivity and resistivity were analyzed. Effects of electrode system, distance between electrodes and the rate of voltage rise on dielectric properties of insulating oil were evaluated in accordance with ASTM D877 and ASTM D1816 standards. Breakdown voltages of insulating oil measured using both VDE (Verband Deutscher Elektrotechniker) electrodes and disk electrodes were compared in conformity with measurement standards. Measurements of dissipation factor, dielectric losses and relative permittivity were performed with IEC 60247 standard considering environmental temperature, applied voltage, power and higher frequency values that satisfy operating conditions. Resistivity of mineral oil also was calculated by using the results of the measurements. In the study, a detailed analysis of mineral oil at real operating conditions was realized. These results contribute to explore insulating characteristic of mineral oil in service.
Keywords: Insulating liquids; Breakdown voltage; Dielectric dissipation factor; Dielectric losses; Relative permittivity; Resistivity; TRANSFORMER LIQUIDS; POWER TRANSFORMERS; FIELD TRANSFORMER; PAPER INSULATION; BREAKDOWN; VOLTAGE; TEMPERATURE; Engineering